Biology of the pathogenic yeast Candida glabrata - Bialková, A; Subík, J (Folia microbiologica, 2006)
The yeasts, being favorite eukaryotic microorganisms used in food industry and biotechnologies for production of biomass and various substances, are also used as model organisms in genetic manipulation, molecular and biological research. In this respect, Saccharomyces cerevisiae is the best-known species but current situation in medicine and industry requires the use of other species. Here we summarize the basic taxonomic, morphological, physiological, genetic, etc. information about the pathogenic yeast Candida glabrata that is evolutionarily very closely related to baker's yeast.
Keywords: mnohočetná fungální léková rezistence; lidé; Drug Resistance, Multiple, Fungal; Humans; Candida glabrata; Candidiasis; kandidóza